Modernizing Bank Regulation in Support of Financial Deepening : The Case of Uruguay - Wezel, Torsten (IMF Working Papers; Working Paper ;, 2009)
This paper studies how Uruguay's regulatory framework was gradually strengthened to address shortcomings identified during the 2002-03 crisis, to align with international standards and, more recently, to deal with cyclical pressures resulting in an acceleration of bank lending. In particular, regulatory reforms pertaining to loan classification and provisioning as well as liquidity requirements are reviewed and evaluated against best practices. The paper concludes that prudential regulation in Uruguay now generally conforms to high standards while also embracing innovative elements such as dynamic provisioning.